Handbook of Plant Growth: pH as the Master Variable - Rengel, Zdenko (Marcel Dekker, 2012)
This reference explores the molecular, biochemical, functional, structural, and developmental mechanisms of pH in plant growth - examining the role of pH in plant symplasm, plant apoplasm, the rhizosphere, the ecosystem, and plant interaction with biotic and abiotic environments.